Reevaluating Conventional Strategies: Harnessing Traditional Structures to Counter Violent Extremism in Pakistan - Sardar Jehanzaib Ghalib (NUST Journal of International Peace and Stability)
Civil-military relations constitute a complex area of international relations through the interaction of military institutions, civil society, and other governmental bureaucracies. Civil-military relations investigate the dynamics of engagement between the military and the general public, as well as the obligation of society to scrutinize the foreign and military strategies of the government. Traditional structures, including informal associations, ethical standards, and communal conventions, have played a pivotal role in Pakistan’s efforts to quell violent insurgencies. These structures have substantially contributed to effectively eliminating extremist ideologies in cooperation with the military. The article explores the significance of a collaborative partnership between traditional structures and military organizations in combating insurgency and, ultimately, successfully eliminating terrorism. Three fundamental groups compose the traditional political system in Pakistan: the Jirga, the Lashkar, and the Clergy. Since 2012, this structure has been employed by the military across multiple tiers to suppress insurgencies, predominantly in the FATA, Swat region, Dir, and other districts where the authority of the state is at risk. The strategic alliance between the military and traditional structures is critical for combating insurgency.